250 AVXS-101 phase 3 study in spinal muscular atrophy type 1. Issue 12 (14th November 2019) - Day, John W; Chiriboga, Claudia A; Crawford, Thomas O; Darras, Basil T; Finkel, Richard S; Connolly, Anne M; Iannaccone, Susan T; Kuntz, Nancy L; Peña, Loren DM; Schultz, Meredith; Shieh, Perry B; Smith, Edward C; et al.
Abstract : Background: Onasemnogene abeparvovec (AVXS-101), a one-time intravenous gene-replacement therapy, treats the genetic root cause of spinal muscular atrophy (SMA). In the phase 1 study, AVXS-101 dramatically improved survival, motor function, and motor milestone achievement in SMA type 1 (SMA1) patients. Methods: STR1VE is a phase 3, multicenter, open-label study (NCT03306277 ) in SMA1 patients <6 months (bi-allelic survival motor neuron 1 gene [ SMN1 ] mutations/deletions, 2 SMN2 copies). Primary outcomes are independent sitting ≥30 seconds at 18 months of age, and survival (no death/permanent ventilation) at 14 months. Secondary outcomes include ability to thrive and ventilatory support at 18 months. Exploratory outcomes include CHOP-INTEND and Bayley-III. Results: Enrollment is complete (22 patients dosed). Mean age at symptom onset, genetic diagnosis, and enrollment was 1.9 (0–4.0), 2.1 (0.5–4.0), and 3.7 (0.5–5.9) months. At baseline, no patient required ventilatory/nutritional support. Mean baseline CHOP-INTEND: 32.6 (17.0–52.0) points; increased by 6.9 (-4.0–16.0), 9.2 (0–18.0), and 11.7 (-3.0–23.0) points at 1, 2, and 3 months; independent sitting: 11/22 patients; survival at 13.6 months: 13/15 (87%) (8 March 2019 datacut). Conclusions: Preliminary data from the AVXS-101 phase 3 study show rapid motor function improvements in SMA1 patients, paralleling phase 1 findings.